(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
Abstract: Considering the legal discourse as “the locus of phrasem understanding”, our paper begins with the definition and the typology of verbal collocations (lexical collocations vs conceptual collocations). Then, we focus our pragmatic-discursive analysis exclusively at the level of conceptual verbal collocations. In fact, we pursue two objectives: (1) to link the study of terminology to phraseology through the passage of specialized terms in conceptual verbal collocations and (2) to study the pragmatic-discursive role of conceptual verbal collocations as a unity factor of legal discourse. Analysing the legal field, the specialized literature emphasized that the terminology and word order are two elements of equal importance for the meaning of the message (Darbelnet, 1979) and that the means of word-formation in legal terminology are similar to those established in the areas of general or specialized language (Cornu, 1990; González-Rey, 2002; Giráldez, 2010, etc.).